Enhanced photocatalytic and antibacterial ability of Cu-doped anatase TiO2 thin films: theory and experiment. - Alotaibi,AM; Williamson,BAD; Sathasivam,SS; Kafizas,A; Alqahtani,M; Sotelo-Vazquez,C; Buckeridge,J; Wu,J; Nair,SP; Scanlon,DO; Parkin,IP (ACS Applied Materials and Interfaces, 2020)
Multifunctional thin films which can display both photocatalytic and antibacterial activity are of great interest industrially. Here, for the first time, we have used aerosol assisted chemical vapour deposition (AACVD) to deposit highly photoactive thin films of Cu-doped anatase TiO2 on glass substrates. The films displayed much enhanced photocatalytic activity relative to pure anatase, and showed excellent antibacterial (vs S.Aureus and E.Coli) ability. Using a combination of transient absorption spectroscopy (TAS), photoluminescence (PL) measurements and hybrid density functional theory calculations, we have gained nanoscopic insights into the improved properties of the Cu-doped TiO2 films. Our analysis has highlighted that the interactions between substitutional and interstitial Cu in the anatase lattice can explain the extended exciton lifetimes observed in the doped samples, and the enhanced UV/visible light photoactivities observed.